Oil palm frond decomposition and soil carbon stocks in response to fertilization regime and management zones - Wandri, Ruli; Hairiah, Kurniatun; Suprayogo, Didik; van Noordwijk, Meine; Asmono, Dwi (Brawijaya University, 2025)
Oil palm plantations face sustainability challenges with variable yields and significant greenhouse gas emissions. To optimize nutrient cycling while maintaining soil carbon stocks, this study investigated the effects of fertilization intensity and spatial management on organic matter decomposition. A factorial experiment in South Sumatra (Indonesia) used a completely randomized block design with three fertilization levels (low, intermediate, high). Decomposition was monitored in three spatial zones (weeded circle, frond stack, interrow) using litter bags over 52 weeks, with sequential harvesting at 13 time points. Soil properties, litter quality, and environmental factors were analyzed using ANOVA and regression models. Results showed decomposition constants ranging from 0.0180 to 0.0258 week?¹ and half-life times of 16 to 32 weeks, with high fertilization treatments accelerating decomposition by 28% but reducing soil carbon (2.05% to 2.77%) below the litter bags compared to low fertilization (4.37%). Frond stack zones exhibited 35% faster decomposition while maintaining higher carbon levels. The regression model combining soil and frond C/N ratios explained 73% of the variance in decomposition. These findings reveal trade-offs between rapid nutrient cycling and carbon storage, demonstrating that sustainable oil palm production requires precision spatial management rather than uniform high fertilization. This study recommends implementing reduced-intensity inorganic fertilization, avoiding nutrient application in frond stacking zones, and expanding organic matter placement in inter-row areas. Future research should prioritize quantifying belowground carbon dynamics and fine root turnover to develop management frameworks balancing immediate productivity with long-term sustainability.